Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1039/c1cp21159e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of perfect, vacancy-doped, and nonmetal adsorbed MoSe2, MoTe2 and WS2 monolayers

Abstract: Very recently, two-dimensional nanosheets of MoSe(2), MoTe(2) and WS(2) were successfully synthesized experimentally [Science, 2011, 331, 568]. In the present work, the electronic and magnetic properties of perfect, vacancy-doped, and nonmetal element (H, B, C, N, O, and F) adsorbed MoSe(2), MoTe(2) and WS(2) monolayers are systematically investigated by means of first-principles calculations to give a detailed understanding of these materials. It is found that: (1) MoSe(2), MoTe(2) and WS(2) exhibit surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
285
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 458 publications
(333 citation statements)
references
References 39 publications
37
285
2
Order By: Relevance
“…It is well established that sulfur vacancies constitute the main source of disorder in MoS 2 [13][14][15][16][17][18]. The formation energies and thermodynamics of these defects have been thoroughly studied [19], but their influence on transport and optical properties remains largely unexplored.…”
Section: Monolayers Of Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that sulfur vacancies constitute the main source of disorder in MoS 2 [13][14][15][16][17][18]. The formation energies and thermodynamics of these defects have been thoroughly studied [19], but their influence on transport and optical properties remains largely unexplored.…”
Section: Monolayers Of Mosmentioning
confidence: 99%
“…Recent experimental as well as theoretical studies have demonstrated that sulfur vacancies are the dominant source of disorder in MoS 2 [13][14][15][16][17][18]. In the following we will therefore focus exclusively on sulfur vacancies, and calculate their effect on the VHC.…”
Section: Disordered Mosmentioning
confidence: 99%
“…Nevertheless, the sulphur vacancy is the predominant point defect compared to Mo vacancy, regardless of the type of preparation method. 18 The effects of point defects on the electronic structure of LTMDs have also been theoretically studied by several groups using first principles calculations 16,17,[19][20][21][22][23][24][25] and 6-band tight-binding (TB) model 26 . Although, ab initio methods based on density functional theory (DFT) can achieve a good degree of accuracy to describe the electronic structure of pristine LTMD materials, they are limited in their application by the presence of defects in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike semimetallic graphene, pristine monolayers of MX 2 are direct band gap semiconductors with band gap values ranging from 1.1 to 1.9 eV. [5][6][7][8][9] With relative fabrication easiness, chemical stability, relatively high mobility, and strong spin-orbit coupling (SOC), these materials are expected to have a significant impact on next-generation ultrathin electronic, optoelectronic, and valleytronic devices. 10-13 3 Following the known theoretical verification of quantum spin Hall (QSH) effect in 2D topological insulators (TIs) graphene, 14 extensive effect has been devoted to the search for new 2D materials or new schemes to obtain 2D TIs with large band gaps.…”
Section: Introductionmentioning
confidence: 99%